2018
DOI: 10.1007/s00436-018-6112-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey on cystic echinococcosis in wild boar from Central Italy

Abstract: Despite the wide distribution of wild boar populations in Italy and the increase of its diffusion in urbanized areas, only one case report has described the occurrence of Echinococcus granulosus s.l. in a wild boar from Marche (Central Italy). The present study investigated the presence of E. granulosus sensu lato with an epidemiological survey on wild boars from central Italy that had been killed during hunting season. Seven hundred sixty-five (765) adult wild boars were examined during the 2016-2017 hunting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…In central Italy, Di Nicola et al (2015) revealed a prevalence of 6% among 101 analysed wild boars from Abruzzo and Lazio regions, whereas recently Di Paolo et al (2017) reported for the first time the genotype G3 in wild boar in Europe. In a recent epidemiological survey, Paoletti et al (2018) showed a prevalence of 1.0% (8/765) for G1 with a fertility rate of 0.3% from central Italy. In the present study we reported an overall prevalence of 4.4% and a fertility rate of 0.9%, three times higher than that found in central Italy by Paoletti et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In central Italy, Di Nicola et al (2015) revealed a prevalence of 6% among 101 analysed wild boars from Abruzzo and Lazio regions, whereas recently Di Paolo et al (2017) reported for the first time the genotype G3 in wild boar in Europe. In a recent epidemiological survey, Paoletti et al (2018) showed a prevalence of 1.0% (8/765) for G1 with a fertility rate of 0.3% from central Italy. In the present study we reported an overall prevalence of 4.4% and a fertility rate of 0.9%, three times higher than that found in central Italy by Paoletti et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…was reported in Spain (Martin-Hernando et al, 2008), Italy (Di Paolo et al, 2017) and France (Corsica) (Umhang et al, 2014). The data in Italy on the sylvatic cycle by epidemiological investigations on the diffusion of CE are scarce and only two studies have reported E. granulosus s.s. genotypes G1 and G3 in wild boars from non-endemic areas (Di Paolo et al, 2017; Paoletti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fertile hydatid cyst PSC viability, that is, the percentage of live PSC, varies between 100% and 2,8% [13][14][15][16][17]. Contrarily, infertile hydatid cysts (also called sterile hydatid cysts [18][19][20][21][22][23]), have no PSC neither attached to the germinal layer nor floating free in the hydatid fluid, and thus are unable to continue with the parasite life cycle. The reason behind why infertile hydatid cysts are unable to produce PSC remains unclear [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the wild boar, as a contamination source for echinococcosis in wild carnivores, could not be ruled out. Indeed, the ovine genotype G1 of E. granulosus was recently described in 8 out of 765 wild boars examined during hunting season in Central Italy (Paoletti et al 2019).…”
Section: Discussionmentioning
confidence: 99%